Communication–Electrochemical Evaluation of MnxFe1-xPO4 (0 ≤ x ≤ 1) Cathode Materials for Na-Ion Batteries. Issue 5 (27th January 2016) - Giner, M.; Roddatis, V.; López, C. M.; Kubiak, P.
Abstract : We report the electrochemical properties of carbon-coated particles of Mnx Fe1-x PO4 (0 ≤ x ≤ 1), a group of promising cathode's materials for sodium-based batteries. The Mnx Fe1-x PO4 materials have been obtained by electrochemical delithiation of LiMnx Fe1-x PO4 and their electrochemical properties have been evaluated in Na cells. The mechanism of Na insertion/extraction strongly depends on the amount of manganese in the structure: at low amount of Mn (x ≤ 0.2) there is no specific domain associated to the electrochemical activity of Mn; at high amount of Mn (x ≥ 0.5) one can distinguish two voltage regions, one linked to the Mn 2+ /Mn 3+, and the other one to the Fe 2+ /Fe 3+ redox couples.